Land use balance for urban economy: A multi-scale and multi-type perspective. (April 2019) - Han, M.Y.; Chen, G.Q.; Dunford, M.
Graphical abstract: Embodied land balance flows for the urban economy. Highlights: Multiple types of land use are assessed by a multi-scale input-output analysis. There is a huge gap between urban land requirement and actual land occupation. The total embodied land transfers related to Beijing are about 41.86 million ha. Sources and destinations of embodied land at urban economy are decomposed. Multi-scale assessment is essential for regional development and land utilization. Abstract: In a situation in which land is in short supply, attention has focused largely on the direct use rather than on the indirect use of land embodied in regional, national and international flows of goods and services. To fill this gap, the multi-scale input-output method is used to identify the impact of final demand and trade activities on the requirements of a single metropolis, Beijing as a case, for land use embodied in its supply chains and commodity trade. While Beijing has limited land at its disposition, the land embodied in its final demand exceeds its own land area by a factor of more than ten, indicating the importance of co-ordinated land use planning and of supporting assessments of land use balance. Covering both direct and indirect land utilization through supply chains, the multi-scale land use analysis plays a significant role to extend the urban land use planning to different scales' sources and sinks. It is thus essential to identify land use balance at urban economy, which could provide potential policy implications for dynamic adjustments of land use allocation and land-intensive industries from a multi-scale and multi-type perspective.